Video analysis of the mechanisms for ankle injuries in football - Andersen, T. E.; Floerenes, T. W.; Arnason, A.; Bahr, I. A. (The American Journal of Sports Medicine, 2004)
BACKGROUND: Although ankle sprains are frequent in football, little is known about their mechanisms. PURPOSE: To describe the injury mechanisms for ankle injuries in male elite football. STUDY DESIGN: Prospective cohort study. METHODS: Videotapes and injury information were collected for 313 of 409 matches from Norwegian and Icelandic elite football during the 1999 to 2000 seasons. Video recordings of incidents that resulted in ankle injuries were analyzed and cross-referenced with injury reports from the team medical staff. RESULTS: A total 46 acute ankle injuries were reported to have occurred, that is, 4.5 injuries per 1000 match hours. Of these, 26 (57%) were identified on the videotapes. Two mechanisms thought to be specific to football were found: 1) player-to-player contact with impact by an opponent on the medial aspect of the leg just before or at foot strike, resulting in a laterally directed force causing the player to land with the ankle in a vulnerable, inverted position; and 2) forced plantar flexion where the injured player hit the opponent's foot when attempting to shoot or clear the ball. CONCLUSIONS: Systematic video analysis provides detailed information on the mechanisms for ankle injuries in football-for lateral ligament sprains and for the condition dubbed "footballer's ankle."